Enhanced auditory spatial localization in blind echolocators. (January 2015) - Vercillo, Tiziana; Milne, Jennifer L.; Gori, Monica; Goodale, Melvyn A.
Abstract: Echolocation is the extraordinary ability to represent the external environment by using reflected sound waves from self-generated auditory pulses. Blind human expert echolocators show extremely precise spatial acuity and high accuracy in determining the shape and motion of objects by using echoes. In the current study, we investigated whether or not the use of echolocation would improve the representation of auditory space, which is severely compromised in congenitally blind individuals (Gori et al., 2014 ). The performance of three blind expert echolocators was compared to that of 6 blind non-echolocators and 11 sighted participants. Two tasks were performed: (1) a space bisection task in which participants judged whether the second of a sequence of three sounds was closer in space to the first or the third sound and (2) a minimum audible angle task in which participants reported which of two sounds presented successively was located more to the right. The blind non-echolocating group showed a severe impairment only in the space bisection task compared to the sighted group. Remarkably, the three blind expert echolocators performed both spatial tasks with similar or even better precision and accuracy than the sighted group. These results suggest that echolocation may improve the general sense of auditory space, most likely through a process of sensory calibration. Highlights: Congenitally blind non-echolocators have a severe deficit in auditory spatial perception. The daily use of echolocation can recover this spatial deficit. Expert blind echolocators also show enhanced spatial auditory sensitivity than sighted individuals. Echolocation is one of the most effective mobility tools for the blind.